How and why “the declared defense of history” by Dubravka Stojanović and Husnija Kamberović collapsed - VASIĆ, Dragiša D. (CURRENTS OF HISTORY, 2021)
An article by Dragiša D. Vasić on drastic examples of the politicization and mythmaking of the Bosniak historical narrative, and polemical essays by Dubravka Stojanović and Husnija Kamberović were published in the journal Tokovi istorije in 2/2020 and 3/2020 issues. This paper analyzes the polemics in light of the declaration called “Defend History”, published in 2020 by a group of historians from the post-Yugoslav area, including Dubravka Stojanović and Husnija Kamberović. The paper demonstrates the pamphleteerist character of the declaration and numerous abuses of history, as well as its ideological and political background.Summary: Husnija Kamberović and Dubravka Stojanović celebrated historiography at the third History Fest held in the Gazi Husrev-beg hall of the Bosniak Institute in Sarajevo in 2019. After that, under the slogan “entity/entities must die” they went to “Petar Kočić” Stage of the National Theatre of Republika Srpska in Banja Luka to discuss “historiography as precursor and/or follower” of politics and ideology. A year later, trembling with anger and bias, on the pages of Tokovi istorije they bitterly denounced a paper discussing examples of politicization and mythmaking of the Bosniak  historical narrative. They ripped Bosniak historiography out of that narrative, claiming it did not exist. They constructed this non-existent, illogical narrative as “monolithic and homogeneous” and subjected it to “a single, political goal”, only to subsequently defend it – Dubravka Stojanović defending it from Dragiša Vasić and Husnija Kamberović defending it from Dragiša D. Vasić, who had not even attacked it. They thus demonstrated the abuses of history which they denounced that same year in a declaration called “Defend History”. By sacrificing scholarly principles for ideological and political purposes formulated as “entity/entities must die”, they took their hats off and did not keep silent.